Antibacterial and immunoregulatory activity of a novel hepcidin homologue in diploid hybrid fish (Carassius auratus cuvieri ♀ × Carassius auratus red var ♂). Issue 98 (March 2020) - Luo, Sheng-Wei; Luo, Zi-Ye; Yan, Teng; Luo, Kai-Kun; Feng, Ping-Hui; Liu, Shao-Jun
Abstract: Hepcidin, a multifunctional hormone oligopeptide, not only exhibits a regulatory role in iron metabolism, but also participates in the regulation of teleostean immunity. In this study, ORF sequence of WR-hepcidin was 258 bp and encoded 85 amino acid residues. Tissue-specific analysis revealed that the highest expression of WR-hepcidin was observed in liver. Aeromonas hydrophila challenge can sharply increased WR-hepcidin mRNA expression in liver, trunk kidney and spleen. The purified WR-hepcidin fusion peptide can directly bind to A. hydrophila and Streptococcus agalactiae, reduce the relative bacterial activity, limit bacterial growth and attenuate their dissemination to tissues in vivo . In addition, the treatment of WR-hepcidin fusion protein can diminish the production of pro-inflammatory cytokines. These results indicated that WR-hepcidin can play a negative regulatory role in bacteria-stimulated pro-inflammatory cytokines production and MyD88-IRAK4 activation. Highlights: We characterized a novel hepcidin gene in hybrid crucian carp. The up-regulation of WR-hepcidin was observed following bacterial challenge. WR-hepcidin can bind to gram positive and gram negative bacteria. WR-hepcidin can restrict the bacterial growth and reduce bacteria-stimulated inflammatory response.